Yersinia Infection with Clostridium Difficile Colitis. (1st February 1989) - Fishman, M.J.; Noble, M.A.; Freeman, H.J.
Abstract : Antibimic associated diarrhea appears to be largely due to Closcridium difficile and may have, at least in part. a toxin mediated pathogenesis. Because a poor correlation exists between measurable toxin titres and symptoms, additional copathogenic factors may be important. All patients seen during a two year period with diarrhea within four weeks of antibiotic therapy, a positive tool culture for C difficile and a positive stool cytotoxin assay specific for C difficile were investigated. All patients had stools cultured for cnteric bacterial pathogens including Salmonella, Shigella. Campylobacter, Aeromonas and Yersinia species. Seven patients had Yersinia species isolated during the course of their illness; no other entcric pathogens were identified. In four patients, Y enrerocolitica was cultured simultaneously with C difficile prior to treatment, and in one of these, Y fredriksenii was also isolated. Of six patients with persistent or recurrent sympcoms after treatment for C difficile ( ie, vancomycin in five and mecronidazole in one patient), four had positive yersinia cultures at the conclusion of therapy ( Y enrerocolitica in three and Y fredriksenii in two patients). All but one of these patients had been yersinia culture negative prior to therapy for C difficile Patients with and without yersinia isolates were then compared with respect to age, sex, clinical symptoms and sigmoldoscopic as well as rectal biopsy findings. The presence of yersinia was associated with male sex, younger age and abdominal pain; other features including hematochezia, fever, arthralgia, cytotoxin titre, sigmoidoscopy and rectal biopsy could not distinguish patients with and without Yersinia species. Thus, ycrsinia may be associated with an antibiotic related diarrheal illness usually attributed to C difficile alone and may be observed in the setting of persistent or recurrent symptoms following treatment for C difficile diarrhea.